Data of microstructure and mechanical properties of carbon foams derived from sucrose/polyacrylamide hydrogel - Yao, Yao (Data Brief, 2016)
An easy method that combined gel casting and physical foaming was used to fabricate modified carbon foams. The design of carbon foams from sucrose/polyacrylamide hydrogel is a new concept for controlling the microstructure and improving the compressive properties of carbon foams. This article provides the micrographs obtained from optical and scanning electron microscope for foaming solution and carbon foams. Weight loss data used to construct the thermo-gravimetric curves are included. Load–displacement data constructing the stress–strain curves and the derived compressive properties are also included.